Sistem Pendukung Keputusan Penentuan Lokasi Industri Berbasis Spasial Menggunakan Metode MOORA - Agusta Praba Ristadi Pinem; Henny Indriyawati; Basworo Ardi Pramono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Information technology is developing rapidly and the effect is every single organization will always collect data and information. The information collected is used as a basis for decision making. But not all information can be directly used for the decision making process. Method and weighting are needed in the process of getting information. One method that can be used to support the decision making process is Multi-Objective Optimization on the basis of Ratio Analysis (MOORA). MOORA is included in the Multi Criteria Decision Making (MCDM) which makes it possible to provide the best choice of information from several choices by using criteria values. This research uses the MOORA method as determining strategic industrial locations by combining spatial data. In determining the strategic location of the industry, MOORA uses several criteria and different weights for each criteria. The MOORA with spatial data can be produce the right information related to the determination of strategic industry locations by finding the correlation between method results with industry location in Semarang city. The results obtained from this research are the formation of a decision support system modeling of industrial location determination using the MOORA method with spatial data. Correlation value generated by the Spearman Rank method is 0,9.